Baricitinib, Methotrexate, or Combination in Patients With Rheumatoid Arthritis and No or Limited Prior Disease‐Modifying Antirheumatic Drug Treatment. Issue 3 (27th February 2017) - Fleischmann, Roy; Schiff, Michael; van der Heijde, Désirée; Ramos‐Remus, Cesar; Spindler, Alberto; Stanislav, Marina; Zerbini, Cristiano A. F.; Gurbuz, Sirel; Dickson, Christina; de Bono, Stephanie; Schlichting, Douglas; Beattie, Scott; et al.
Abstract : Objective: We undertook this phase III study to evaluate baricitinib, an orally administered JAK‐1/JAK‐2 inhibitor, as monotherapy or combined with methotrexate (MTX) compared to MTX monotherapy in patients with active rheumatoid arthritis (RA) who had received no or minimal conventional synthetic disease‐modifying antirheumatic drugs (DMARDs) and who were naive to biologic DMARDs. Methods: A total of 588 patients were randomized 4:3:4 to receive MTX monotherapy (once weekly), baricitinib monotherapy (4 mg once daily), or the combination of baricitinib and MTX for 52 weeks. The primary end point assessment was a noninferiority comparison of baricitinib monotherapy to MTX monotherapy based on the proportion of patients meeting the American College of Rheumatology 20% improvement criteria (achieving an ACR20 response) at week 24. Results: The study met its primary objective. Moreover, baricitinib monotherapy was found to be superior to MTX monotherapy at week 24, with a higher ACR20 response rate (77% versus 62%; P  ≤ 0.01). Similar results were observed for combination therapy. Compared to MTX monotherapy, significant improvements in disease activity and physical function were observed for both baricitinib groups as early as week 1. Radiographic progression was reduced in both baricitinib groups compared to MTX monotherapy; the difference was statistically significant for baricitinib plus MTX. The rates of serious adverse events (AEs) were similar across treatment groups, while rates of some treatment‐emergent AEs, including infections, were increased with baricitinib plus MTX. Three deaths were reported, all occurring in the MTX monotherapy group. Malignancies, including nonmelanoma skin cancer, were reported in 1 patient receiving MTX monotherapy, 1 receiving baricitinib monotherapy, and 4 receiving baricitinib plus MTX. Conclusion: Baricitinib alone or in combination with MTX demonstrated superior efficacy with acceptable safety compared to MTX monotherapy as initial therapy for patients with active RA.